PENGARUH NILAI TUKAR DOLLAR/RUPIAH DAN PRODUKSI TEKSTIL TERHADAPIMPOR KAPAS DI JAWA TENGAH - Meidina Masiana Arofina; Yusmar Ardhi Hidayat; Sri Eka Sadriatwati (JOBS (Jurnal Of Business Studies), 2016)
A large number of textile industry in Central Java increasing the demand for cotton as a raw material. However, the high demand for cotton is not followed by a large quantity of cotton production in domestic country. The problem statement in this research is how the influence of dollar/rupiah’s exchange rate and textile production toward cotton import in Central Java. The purpose in this research are to analyze the influence of dollar/rupiah’s exchange rate and textile production toward cotton import in Central Java. The independentvariablesin this researcharedollar/rupiah’s exchangerateand textile production, while the dependentvariable is cotton import in Central Java.Thedata that were used was secondary data during period 2009-2013 in monthly, the type of data were used quantitative data, time series data, and ratio data. The results of this research show that dollar/rupiah’s exchange rate and textile production simultaneously had significant influence toward cotton import in Central Java. Nevertheless, partially only textile production has significant and positive influence toward cotton import in Central Java. So, cotton is a derived demand, because it depends indirectly on the demand for the product.  Then, dollar/rupiah’s exchange rate has not significant and negative influence toward cotton import in Central Java. So that, cotton is an elasticity product and the availability of cotton became the important thing.